2017
DOI: 10.18203/2320-1770.ijrcog20174028
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining successful intrauterine insemination

Abstract: Background: Infertility is defined as failure to conceive even after one year of regular, frequent and unprotected intercourse. Infertility can be attributed to male causes in approximately 25-40% cases, female causes in 40-50% cases, both in 10-20% and unexplained causes in 10-15% cases. Artificial insemination (Intrauterine Insemination) involves placement of processed sperms from husband (AIH – artificial insemination homologous) or from donor (AID – artificial insemination donor) into the female genital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…In this study, there was no significant difference in the age of males between the pregnant and non-pregnant groups. This finding is in agreement with several studies (11,19,27,29).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, there was no significant difference in the age of males between the pregnant and non-pregnant groups. This finding is in agreement with several studies (11,19,27,29).…”
Section: Discussionsupporting
confidence: 94%
“…The results of our study showed that the pregnancy rate with IUI was 23.4% for each couple (82/350). This is similar to the results of (23.5%) Sinha et al (19) and is in line with other studies (15,20,21).…”
Section: Discussionsupporting
confidence: 94%
“…The results of our study showed that the pregnancy rate with IUI was 23.4% for each couple (82/350). This is similar to the results of (23.5%) Sinha et al (19) and is in line with other studies (15,20,21).…”
Section: Discussionsupporting
confidence: 94%
“…It can be classified into artificial insemination by husband (AIH) and artificial insemination by donor (AID) according to the source of the sperm. There are many factors influencing the clinical pregnancy rate following IUI, including age, infertility type, sperm quality, mature follicular number, endometrial thickness, and so on (3)(4)(5)(6)(7). However, the prognostic values of these factors remain controversial.…”
Section: Introductionmentioning
confidence: 99%